Association of renal resistive index with aortic pulse wave velocity in hypertensive patients. (29th August 2020) - Geraci, Giulio; Mulè, Giuseppe; Geraci, Calogero; Mogavero, Manuela; D'Ignoto, Francesco; Morreale, Massimiliano; Foraci, Anna Carola; Cottone, Santina
Abstract: Background: Recent data suggest that renal haemodynamic parameters obtained by duplex Doppler sonography, especially the intrarenal resistive index (RI), may be associated with systemic vascular changes. However, conflicting data exist about the independent relationship between aortic stiffness and RI. The aim of this study was to evaluate the relationship between RI and arterial stiffness, assessed by aortic pulse wave velocity (aPWV), in hypertensive patients. Design: Cross-sectional study. Methods: We enrolled 264 hypertensive subjects aged between 30 and 70 years. They were divided into two groups, either with normal renal function ( n  = 140) or with chronic kidney disease (CKD) ( n  = 124). Each patient underwent assessment of ultrasonographic renal RI and measurement of aPWV through oscillometric device. Results: Patients with renal RI>0.7 showed higher values of aPWV, both in the overall population ( p  < 0.001) and in the subgroups with ( p  < 0.01) and without CKD ( p  < 0.01). Moreover, statistically significant correlations were observed between aPWV and RI in the whole population ( r  = 0.38, p  < 0.001) and in the subgroups with ( r  = 0.35, p  < 0.001) and without CKD ( r  = 0.31, p  < 0.001). These correlations held even after adjustment for several confounding factors in multivariate analyses. Conclusions: Our results seem to corroborate the concept that the RI may be considered as a marker of systemic vascular changes and therefore a predictor of cardiovascular risk.